Food choice motives and diet quality in Korean adults: sex- and age-specific associations with implications for health promotion - Hyejin Chun; Jung-Heun Ha; Miae Doo (BMC Public Health, 2026)
Abstract Objectives To examine associations between food choice motives and diet quality in Korean adults and whether these associations vary by sex and age. Methods We analyzed cross-sectional data from an online survey of adults aged 20–64 years in Korea ( n = 1,829). Food choice motives were assessed using the 36-item Food Choice Questionnaire and summarized as three empirically derived factor scores (Health/Naturalness, Convenience/Price, Mood/Sensory). Diet quality was measured using the Nutrition Quotient for adults (NQ-2021). Multivariable linear regression models included all three motive factors and adjusted for sex, age, body mass index, and educational level, with effect modification assessed using interaction terms and stratified analyses. Results In the fully adjusted model, Health/Naturalness motives were positively associated with diet quality (β = 9.03; 95% CI: 8.13, 9.93), whereas Convenience/Price (β=−3.40; 95% CI: −4.55, − 2.25) and Mood/Sensory motives (β=−2.48; 95% CI: −3.57, − 1.40) were inversely associated. The inverse association for Convenience/Price motives was stronger in women than men (p-interaction = 0.022), and age-group effect modification was observed for Health/Naturalness ( p -interaction = 0.002) and Mood/Sensory motives ( p -interaction = 0.018). Conclusions Food choice motives were associated with diet quality, with modest variation by sex and age group. These patterns may inform the development and prospective evaluation of subgroup-sensitive health-promotion and food-environment strategies.